Long-Term Results of the RAPCO Trials. Issue 14 (6th October 2020) - Buxton, Brian F.; Hayward, Philip A.; Raman, Jai; Moten, Simon C.; Rosalion, Alexander; Gordon, Ian; Seevanayagam, Siven; Matalanis, George; Benedetto, Umberto; Gaudino, Mario; Hare, David L.
Abstract : Background: An internal thoracic artery graft to the left anterior descending artery is standard in coronary bypass surgery, but controversy exists on the best second conduit. The RAPCO trials (Radial Artery Patency and Clinical Outcomes) were designed to compare the long-term patency of the radial artery (RA) with that of the right internal thoracic artery (RITA) and the saphenous vein (SV). Methods: In RAPCO-RITA (the RITA versus RA arm of the RAPCO trial), 394 patients <70 years of age (or <60 years of age if they had diabetes mellitus) were randomized to receive RA or free RITA graft on the second most important coronary target. In RAPCO-SV (the SV versus RA arm of the RAPCO trial), 225 patients ≥70 years of age (or ≥60 years of age if they had diabetes mellitus) were randomized to receive RA or SV graft. The primary outcome was 10-year graft failure. Long-term mortality was a nonpowered coprimary end point. The main analysis was by intention to treat. Results: In the RA versus RITA comparison, the estimated 10-year patency was 89% for RA versus 80% for free RITA (hazard ratio for graft failure, 0.45 [95% CI, 0.23–0.88]). Ten-year patient survival estimate was 90.9% in the RA arm versus 83.7% in the RITA arm (hazard ratio for mortality, 0.53 [95% CI, 0.30–0.95]). In the RA versus SV comparison, the estimated 10-year patency was 85% for the RA versus 71% for the SV (hazard ratio for graft failure, 0.40 [95% CI, 0.15–1.00]), and 10-year patient survival estimate was 72.6% for the RA group versus 65.2% for the SV group (hazard ratio for mortality, 0.76 [95% CI, 0.47–1.22]). Conclusions: The 10-year patency rate of the RA is significantly higher than that of the free RITA and better than that of the SV. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00475488. Abstract : Supplemental Digital Content is available in the text.